Menino de assentamento: ser criança no Assentamento Reunidas - Freitas, Mariana Ferreira (2011)
The present study, which was made at "Assentamento Reunidas", located in Promissão city - São Paulo, has been investigating children and families who live in Agrovila Campinas, a rural settlement at the end of 1980s. In different situations and times, 25 children regularly enrolled in rural schools and their family were interviewed and observed in their routines, their wishes and desires, their moments of entertainment, beliefs and habits. The school was also a topic of study, with its relations and contents stabilished on their rural settlement space. The question for this paper is: What means being a child in this rural settlement and how important the school is for this community?